Evaluation of Residual Stresses in Grinding by Magnetic Barkhausen Noise (The International Journal of Engineering & Information Technology (IJEIT), 2016)
The effect of residual stresses and the lubricanttype in grinding on the characteristics of magnetic Barkhausen noise (MBN) profiles were examined in lowalloy steel of the type used for wear-resistant engineeringcomponents. A shotpeened and ground in differentconditions specimens were tested. MBN measurementsshowed that the intensity of the signal increases with abusivegrinding due to residual tensile stresses and decreases withshot peening due to residual compressive stresses. Anincrease was seen in wet grinding specimens as comparedwith the heat-treated specimen. The increase in MBN aftergrinding was due to local heating with transition from theinitial stage of strong martensitic structure, with residualstress of compression, to the following stage of lowerhardening with tendency to residual stress of tensilecharacter. In addition, Barkhausen signals from surfacesground under controlled conditions were found to bedependent on the lubricant type. The decrease in MBNafter shotpeening was due to the accumulation of residualcompressive stresses introduced to the martensitic structure. The observations are discussed in the light of establishedmodels of Barkhausen noise.